Penile Tuberculosis Associated with Monoclonal Gammopathy of Undetermined Significance - Wilfred C.H. Wu; Shyh-Chyan Chen; Ju-Ton Hsieh; Jun Chen; Hong-Chiang Chang (Journal of the Formosan Medical Association, 2006)
Mycobacterium tuberculosis (TB) infection of the penis is a rare but serious problem. We report a case of penile TB in a 75-year-old man who presented with fever and dyspnea. No active lung lesions except pleural and pericardial effusion were found on chest X-ray. Monoclonal gammopathy of undetermined significance was diagnosed after serum and urine electrophoresis studies, and repeated bone marrow studies. Genital examination showed diffuse papulonecrotic skin ulcers involving the whole penile shaft, extending ventrally to the median raphe of the scrotum. Pus smear showed positive acid-fast stain, and culture yielded M. tuberculosis. Culture of pleural and pericardial effusion was also positive for M. tuberculosis. Anti-TB treatment was given with isoniazid, ethambutol, rifampin and pyrazinamide, and the cutaneous lesion was noted to be healed at follow-up 6 months later. Although rare, the possibility of TB as a cause of genital ulcer should be kept in mind.